Effectiveness enhancement of sugar cane juice fermentation for polyhydroxyalkanoates (PHAs) production - Singhaboot, Pakjirat; Kaewkannetra, Pakawadee (Asia-Pacific Journal of Science and Technology, 2017)
Sugar cane juice (SCJ) was used as a carbon source for polyhydroxyalkanoates (PHAs) production by pure bacterium strain of Azotobactor vinelandii. Its growth and PHAs production were investigated via batch fermentation. Three main types of sugars as glucose, fructose and sucrose were found in the SCJ and then was preliminary tested by A. vinelandii to evaluate its capability for utilizing in each sugar. It was found that bacterium strain could grow in all type of sugars at properly initial concentration of 20 g/l. Subsequently, when the initial total sugar was increased to 40 g/l, the higher dry cell weight (DCW) and PHAs concentration were achieved. Then, effect of air supply on cell growth and PHAs production was further investigated in 5 l fermenter. The maximum PHAs content reached at about 72% when the process was maintained the air flow at 2 vvm without controlled the dissolved oxygen (DO). However, the highest productivity (0.062 g/l/h) was obtained in the controlled condition of air flow (2 vvm) and the DOat 5%. To improve the process, repeated batch fermentation was performed; the PHAs productivity in final batch was reached at about 0.142 g/l/h that was 2.09 fold when compared to the first batch of the process (0.068 g/l/h).